2015
DOI: 10.1186/1471-2393-15-s2-s4
|View full text |Cite
|
Sign up to set email alerts
|

Basic newborn care and neonatal resuscitation: a multi-country analysis of health system bottlenecks and potential solutions

Abstract: BackgroundAn estimated two-thirds of the world's 2.7 million newborn deaths could be prevented with quality care at birth and during the postnatal period. Basic Newborn Care (BNC) is part of the solution and includes hygienic birth and newborn care practices including cord care, thermal care, and early and exclusive breastfeeding. Timely provision of resuscitation if needed is also critical to newborn survival. This paper describes health system barriers to BNC and neonatal resuscitation and proposes solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 71 publications
1
87
0
Order By: Relevance
“…Globally, facility deliveries are not associated with a subsequent reduction in perinatal mortality due to key quality gaps, including inadequate staffing, widespread use of inexperienced trainees as front line workers and overcrowded facilities (12)(13)(14)(15)(16)(17)(18).…”
Section: Key Notesmentioning
confidence: 99%
“…Globally, facility deliveries are not associated with a subsequent reduction in perinatal mortality due to key quality gaps, including inadequate staffing, widespread use of inexperienced trainees as front line workers and overcrowded facilities (12)(13)(14)(15)(16)(17)(18).…”
Section: Key Notesmentioning
confidence: 99%
“…There are no clear guidelines from the government to decide from the state level regarding the rational distribution of human resources on the basis of the delivery load. Under the every newborn action plan, A study was conducted in 12 countries of Asia and Africa that also suggested that newborn resuscitation bottleneck is more severe than for essential newborn care [5]. The study also stated that neonatal resuscitation services are more critical at the district level.…”
Section: Discussionmentioning
confidence: 99%
“…India is also facing the problem regarding lack of availability of trained and skilled health workers in terms of ANMs, SNs and doctors [4]. Redistribution of human resources in the facilities at the district level has a critical role thereafter [5]. Availability of human resources and its distribution in a country has great impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations